Using Movement to Regulate Emotion: Neurophysiological Findings and Their Application in Psychotherapy - Shafir, Tal (Frontiers in Psychology, 2016)
Emotion regulation is a person’s active attempt to manage their emotional state by enhancing or decreasing specific feelings. Peripheral theories of emotion argue that the origins of emotions stem from bodily responses. This notion has been reformulated in neurophysiological terms by Damasio, who claimed that emotions are generated by conveying the current state of the body to the brain through interoceptive and proprioceptive afferent input. The resulting brain activation patterns represent unconscious emotions and correlate with conscious feelings. This proposition implies that through deliberate control of motor behavior and its consequent proprioception and interoception, one could regulate his emotions and affect his feelings. This concept is used in dance/movement (psycho)therapy where, by guiding to move in a certain way, the therapist helps the client to evoke, process, and regulate specific emotions. Exploration and practice of new and unfamiliar motor patterns can help the client to experience new unaccustomed feelings. The idea that certain motor qualities enhance specific emotions is utilized by the therapist also when she mirrors the client’s movements or motor qualities in order to feel what the client feels, and empathize with them. Because of the mirror neurons, feeling what the client feels is enabled also through observation and imagination of their movements and posture. This principle can be used by verbal therapists as well, who should be aware of its bi-directionality: clients seeing the therapist’s motor behavior are unconsciously affected by the therapist’s bodily expressions. Additional implications for psychotherapy, of findings regarding mirror neurons activation, are discussed.